Assessing the Spatial-Temporal Land use Change and Encroachment Activities Due to Flood Hazard in North Coast of Central Java, Indonesia - Imam Setyo Hartanto; Rini Rachmawati (Indonesian Journal of Geography, 2017)
Demak is known as the second largest region suffering land use change in Java’s North Coast. The topographic condition in downstream affects this area becomes susceptible with flood hazard. This research aims to assess the interactions between flooding, land use change and encroachment activities in Mijen and Wedung sub districts, Demak region, Central Java, Indonesia. This research combines the Driving Force, Pressure, State, Impact and Response (DPSIR) analysis. The supervised classification by Maximum Likelihood of time series Landsat images (2000, 2009 and 2014) was chosen for land cover analysis. The land use change shows that paddy field area descended almost 6%, mangrove forest fall 79% meanwhile settlement grown up almost double in 2000-2014. The result of overall accuracy assessment is 78.23%. The DPSIR result shows that land use change not too affect the flood events but floods influence land use pattern in north and south area of Mijen and Wedung.